Rapid Performance Evaluation of Water Supply Services for Strategic Planning - Gulfam Shahzad; Rashid Rehan; Muhammad Fahim (Civil Engineering Journal, 2019)
The assessment of existing water supply services was carried out through selected performance indicators with the aim of using that data in future for strategic planning of urban Mardan. The key performance indictors studied were selected to assess both the quantity and quality of water. The quality of water was assessed by turbidity, pH, and E-coli tests for samples collected at the start, middle, and tail end of the distribution system. The quantity of water supplied was measured by calculating discharges from water tapes at the three selected locations in the distribution system. A total of thirty samples were collected from ten union councils out of fourteen covering urban Mardan. A number of issues are highlighted in the overall water supply infrastructure and short, mid, and long term remedial measures are recommended. The results are presented in the form of an interactive map using Google Earth and VBA based dynamic database. It was found that the overall quality of water is generally acceptable for drinking. However, the presence of bacteria is an issue in many cases which needs to be resolved. A significant decrease in discharge is observed in the distribution systems away from the source due to leakages and illegal connections. A comprehensive overhaul of both management and infrastructure is required for sustainable and satisfactory level of services.